Automatic calculation of symmetry‐adapted tensors in magnetic and non‐magnetic materials: a new tool of the Bilbao Crystallographic Server. Issue 3 (30th April 2019) - Gallego, Samuel V.; Etxebarria, Jesus; Elcoro, Luis; Tasci, Emre S.; Perez-Mato, J. Manuel
Abstract : Two new tools hosted on the Bilbao Crystallographic Server are presented. The programs permit the automatic calculation of symmetry‐adapted forms of tensor properties for magnetic and non‐magnetic groups. The cases of equilibrium, transport, optical and nonlinear optical susceptibility tensors are studied separately. Abstract : Two new programs, MTENSOR and TENSOR, hosted on the open‐access website known as the Bilbao Crystallographic Server, are presented. The programs provide automatically the symmetry‐adapted form of tensor properties for any magnetic or non‐magnetic point group or space group. The tensor is chosen from a list of 144 known tensor properties gathered from the scientific literature or, alternatively, the user can also build a tensor that possesses an arbitrary intrinsic symmetry. Four different tensor types are considered: equilibrium, transport, optical and nonlinear optical susceptibility tensors. For magnetically ordered structures, special attention is devoted to a detailed discussion of the transformation rules of the tensors under the time‐reversal operation 1′. It is emphasized that for non‐equilibrium properties it is the Onsager theorem, and not the constitutive relationships, that indicates how these tensors transform under 1′. In this way it is not necessary to restrict the validity of Neumann's principle. New Jahn symbols describing the intrinsic symmetry of the tensors are introduced for several transport and optical properties. In the case of some nonlinear optical susceptibilities of practical interest, an intuitive method is proposed based on simple diagrams, which allows easy deduction of the action of 1′ on the susceptibilities. This topic has not received sufficient attention in the literature and, in fact, it is usual to find published results where the symmetry restrictions for such tensors are incomplete.